THE EFFECT OF ANXIETY ON FOREIGN LANGUAGE SPEAKING PERFORMANCE - Sadullayeva Parvina Bakhtiyorovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The effect of anxiety on foreign language speaking performance is one of the most widely discussed issues in the field of language learning. When people seek to communicate in a language that is not their mother tongue, they often experience certain psychological barriers that prevent them from speaking fluently and confidently. Among the most common of these barriers is anxiety, a psychological state characterized by nervousness, tension, and self-doubt that manifests acutely when expressing oneself in a foreign language context.